Ionotropic Receptor Genes in Fig Wasps: Evolutionary Insights from Comparative Studies - Hui Yu; Xiaojue Nong; Weicheng Huang; Ling Yang; Chantarasuwan Bhanumas; Yongmei Xiong; Seping Dai (Insects)
The mechanisms of chemoreception in fig wasps (Hymenoptera, Agaonidae) are of primary importance in their co-evolutionary relationship with the fig trees they pollinate. As the supplementary receptors to odorant receptors (ORs) and gustatory receptors (GRs) in insects, we compare the evolutionary characters of ionotropic receptors (IRs) among 25 fig wasp taxa in six genera. In total, we identified 205 IRs in 25 fig wasps, with each taxon recording from 5 to 12 IR genes. We found 189 IR genes clustered into 18 orthologous groups that can be divided into three types: IRco, antennal IRs, and divergent IRs. More IRs belong to antennal IRs in fig wasps, which can be sensitive to acids, aldehydes, polyamines, salt, amino acids, and temperature/humidity according to homology comparison. Additionally, some IR genes in fig wasps do not cluster with those of outgroup species (e.g., Drosophila melanogaster, Apis mellifera), suggesting they may represent a unique group and may have special functions in fig wasps. Divergent IRs are very few, with large sequence variation between species. Compared to ORs and GRs in fig wasps, gene sequences in most IR orthologous groups are more conserved between genera, with the lowest sequence similarity in 10 orthologous groups (including three IRco) exhibiting above 58.5%. Gene sequences are consistent with the phylogenetic relationships among fig wasps, which is the same as ORs and GRs. Strong purifying selection of IR genes was detected, as shown by the low ω values. Signatures of positive selection were detected in loci from three orthologous groups. Our results provide important molecular information for further studies on chemosensory mechanisms in fig wasps.